1973
DOI: 10.1113/jphysiol.1973.sp010236
|View full text |Cite
|
Sign up to set email alerts
|

The influence of body core temperature and peripheral temperatures on oxygen consumption in the pig

Abstract: SUMMARY1. The rate of oxygen consumption was measured in young pigs exposed to different ambient temperatures and the effect on metabolic rate of changing the temperature of thermodes implanted in the hypothalamus and over the spinal cord was determined. In some experiments the temperature of the skin over the trunk was changed by means of a waterperfused coat.2. Cooling the hypothalamus or the spinal cord in a warm ambient did not change the rate of oxygen consumption. At a thermoneutral ambient temperature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1973
1973
2000
2000

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…However, a more pronounced increase in plasma noradrenaline was observed when the spinal cord was cooled. This greater response to spinal cooling is paralleled by the greater increase in metabolic rate during spinal cooling than during cooling of the hypothalamus (Carlisle & Ingram, 1973). The precise significance of these differences cannot be assessed since the exact temperature of the temperature-sensitive neurones was not known, but it seems unlikely that the neurones in the cord were cooler at a thermode temperature of 20 C than those in the hypothalamus were at a thermode temperature of 10 'C.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more pronounced increase in plasma noradrenaline was observed when the spinal cord was cooled. This greater response to spinal cooling is paralleled by the greater increase in metabolic rate during spinal cooling than during cooling of the hypothalamus (Carlisle & Ingram, 1973). The precise significance of these differences cannot be assessed since the exact temperature of the temperature-sensitive neurones was not known, but it seems unlikely that the neurones in the cord were cooler at a thermode temperature of 20 C than those in the hypothalamus were at a thermode temperature of 10 'C.…”
Section: Discussionmentioning
confidence: 99%
“…First, the magnitude of the other thermoregulatory responses observed in the pig after cooling the hypothalamus all increase steadily as the temperature of the thermode changes (Ingram & Legge, 1971Carlisle & Ingram, 1973a), while the response of the thyroid gland seems to be limited to experiments in which the thermode was cooled to 10°C. In investigations involving the rat (Reichlin, 1964) and the goat (Andersson et al 1962) the effects of different degrees of cooling were not systematically assessed, but since there was an appreciable rise in body temperature it is probable that 168 THYROID AND BODY TEMPERATURE the stimulus was a strong one.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of the higher metabolic rate also requires adrenal gland secretions, (13,18,45). Experiments have shown that thyroid hormone· production is counterbalanced by peripheral qegradation .of extrathyroidal hormone which increases as ambient temperature decreases and vice versa, (7,8,9,16,24,25,26,70). Thus the thyroid gland behaves·as though its secretion were essential to the internal environment through a compensatory homeostatic increase in the production of thyroid stimulating hormone when thyroid utilization increases, (16,70).…”
Section: _mentioning
confidence: 99%